ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA MENGGUNAKAN PENDEKATANPEMBELAJARAN MATEMATIKA REALISTIK (PMR) - Sari, Dewi Purnama; Arini, Lilis (Pedagogi: Jurnal Ilmiah Pendidikan, 2024)
ABSTRACT The aim of this research is to find out how students' mathematical connection abilities use the realistic mathematics learning approach (RME) at SMA PAB 5 Klumpang. This type of research is descriptive qualitative research. The research subjects of class X SMA PAB 5 Klumpang consisted of 25 students. The research object was the students' mathematical abilities using a realistic mathematical approach. Data collection techniques used by researchers were observation, interviews and documentation. Data analysis techniques used the Miles and Huberman approach. The level of mathematical connection ability of class Based on the results of research conducted by researchers, it can be concluded that the research subject is (1) students achieve mathematical connection abilities in the high category and are able to produce all indicators in mathematical connection abilities, namely the ability to connect between mathematical topics/concepts, the ability to connect mathematics with other sciences and the ability Mathematical connections to everyday life. (2) students achieve mathematical connection abilities in the low category and are unable to produce a single indicator of mathematical connection abilities. (3) students achieve mathematical connection abilities in the medium category and are able to produce two indicators of mathematical connection abilities, namely the ability to connect between mathematical topics/concepts and the ability to connect mathematics with other sciences.